Insect Pest Control from Chemical to Biotechnological Approach: Constrains and Challenges - Stefano Civolani; Massimo Bariselli; Riccardo Osti; Giovanni Bernacchia (Insects)
The large growth in the global population requires new solutions for the control of harmful insects that compete for our food. Changing regulatory requirements and public perception, together with the continuous evolution of resistance to conventional insecticides, also require, in addition to innovative molecules with different modes of action, new non-chemical control strategies that can help maintain efficient integrated pest management programs. The last 30 years have inaugurated a new era characterised by the discovery of new mechanisms of action and new chemical families. Although European programs also promote a green deal in the crop protection sector, the existing thorough regulations slow down its spread and the adoption of new products. In light of these changes, this review will describe in more detail the dynamics of discovery and registration of new conventional insecticides and the difficulties that the agrochemical industries encounter. Subsequently, the different innovative control strategies alternative to conventional insecticides based on natural substances of different origin, entomopathogenic microorganisms, semiochemical and semiophysical compounds, and classical and augmentative biological control will be described. The advantages of these green strategies will be illustrated and also the constrains to their diffusion and commercialisation. Finally, the main biotechnological discoveries will be described, from transgenic plants to symbiotic control, classical genetic control, and, more recently, control based on insect genomic transformation or on RNAi. These new biotechnologies can revolutionise the sector despite some constrains related to the regulatory restrictions present in different countries.